CURE CHARACTERISTICS AND CROSSLINK DENSITY OF NATURAL RUBBER/STYRENE BUTADIENE RUBBER BLENDS - Indra Surya; Syahrul Fauzi Siregar (Jurnal Teknik Kimia USU, 2014)
By using a semi-efficient vulcanization system, the cure characteristics and crosslink density of natural rubber/styrene butadiene rubber (NR/SBR) blends were studied with a blend ratio from 0 to 100% rubber. The scorch time, optimum cure time, and torque difference value of the blended rubber compounds were determined by using the Moving-Die Rheometer (MDR 2000). The crosslink density was determined by the Flory—Rehner approach. Results indicate that the scorch and cure times, ts2 and t90, of the NR/SBR blends increased with increasing the SBR content. Whilst, the maximum values of torque difference and crosslink density were performed by the NR/SBR blend with a blend ratio of 75/25.